Penerapan Sistem Akuntansi Instansi Berbasis Akrual Sebagai Implementasi PP No. 71 Tahun 2010 pada Politeknik Negeri Pontianak - Zawitri, Sari; Kurniasih, Ninik; Kartikawati, Theresia Siwi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
The government regulation (PP) number 71 year 2010 is a new regulation standard of accounting in the public sector. The new regulation standard that inspiring the writers to the research title: Penerapan Sistem Akuntansi Instansi Berbasis Akrual sebagai Implementasi PP nomor 71 tahun 2010 pada Politeknik Negeri Pontianak. The Problems are formulated as (1) The changes of institutional accounting system (SAI) PP 24 year 2005 into PP 71 year 2010 or cash toward accrual into accrual basis? (2) How preparation and the application transition accrual basis institutional accounting system (SAI) or implementation PP 71 year 2010 of the Politeknik Negeri Pontianak? It"™s concern to disclosure and measurement of Asset, Liabilities, Earned, and Expense. This the exploratory research method which is narrative and descriptive approach with the Politeknik Negeri Pontianak is an object. The results, as form of adjustment in order to change cash toward accrual into accrual basis, accrual accounting recognizes revenues by treasurer expenditure with adding income that still must be accepted in the accounting period during which the service is performed and/or adding unearned revenue. Politeknik Negeri Pontianak almost meets the six conditions that must have preparation and the application transition cash toward accrual into accrual basis of institutional accounting system as implementation PP 71 year 2010 be general conclusion of this research. Writers suggested all parties related in an accounting system institutional of Politeknik Negeri Pontianak commitment to keeping together in the process of financial reporting with accrual basis.